2017
DOI: 10.1016/j.jplph.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Far-red light is needed for efficient photochemistry and photosynthesis

Abstract: The efficiency of monochromatic light to drive photosynthesis drops rapidly at wavelengths longer than 685nm. The photosynthetic efficiency of these longer wavelengths can be improved by adding shorter wavelength light, a phenomenon known as the Emerson enhancement effect. The reverse effect, the enhancement of photosynthesis under shorter wavelength light by longer wavelengths, however, has not been well studied and is often thought to be insignificant. We quantified the effect of adding far-red light (peak a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
174
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 211 publications
(207 citation statements)
references
References 34 publications
29
174
1
3
Order By: Relevance
“…1 and 2) [9]. In addition, the promotive effect of additional Fr radiation on photosynthesis and whole-plant net assimilation was previously reported in lettuce and geranium [12,18]. Together, these results suggested that the high enrichment of Fr light possibly contributed to increased starch and sucrose contents by improving photosynthetic capacity of soybean leaves.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…1 and 2) [9]. In addition, the promotive effect of additional Fr radiation on photosynthesis and whole-plant net assimilation was previously reported in lettuce and geranium [12,18]. Together, these results suggested that the high enrichment of Fr light possibly contributed to increased starch and sucrose contents by improving photosynthetic capacity of soybean leaves.…”
Section: Discussionsupporting
confidence: 67%
“…Plant leaves absorb less amount of Fr light (λ > 700 nm); therefore, it contributes less towards the quantum yield of photosynthesis [17]. However, Zhen and van Iersel [18] reported that Fr light is required for efficient photochemistry and photosynthesis. Similarly, the Fr light of the shade is higher than that of low light, thereby increasing the net photosynthesis rate (P n ) under the same light intensity condition [11], resulting in increased the whole-plant net assimilation [6,9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations